Preconceptual leptin levels in gestational diabetes and hypertensive pregnancy - Antti Peltokorpi; Lisinen Irina; Viikari Liisa; Kaaja Risto (Taylor & Francis Group, 2022)
Pregnancy - induced hypertension (PIH), preeclampsia (PE), and gestational diabetes (GDM) are common adverse outcomes in pregnancy. Objective To find out whether preconceptual leptin levels differ in subsequent pregnancy between control vs. GDM and hypertensive pregnancy groups. Materials and Methods Data was from The Cardiovascular Risk in Young Finns Study and The Medical Birth Register of Finland. Of 293 subjects 71 developed GDM, 27 PIH/PE and 201 were controls. Results Leptin was higher in GDM (p < 0.0001) and PIH/PE (p = 0.0002) groups compared to control. GDM group was robust to BMI matching (p = 0,0081). Conclusion Leptin was higher in GDM (p < 0.0001) and PIH/PE (p = 0.0002) groups compared to control. GDM group was robust to BMI matching (p = 0,0081).